Analysis of Lightning Strike Effects on Crude Oil Storage Tank Protection System at PT. Pertamina Balongan Indramayu - Agus Siswanto; Junaedi Junaedi; Muhamad Soleh; Mudofar Baehaqi (Mestro, 2022)
Main Gathering Station (MGS) Balongan Pertamina EP Asset 3 OGT is an industry engaged in the oil and gas sector by always paying attention to QHSE (Quality, Health, Safety and Environment) aspects. This industry is a national vital object categorized as a zone 1 and zone 2 hazardous area. There is a source of danger that has the potential to cause damage to equipment and people. The electrical installation used is a lightning protection system with reference to the NFPA 780-2017 standard concerning the Standard for the Installation of Lightning Protection Systems. The rolling sphere method is used to calculate the need for a lightning protection system. To calculate the need for a grounding electrode, a rod electrode grounding system is used. Construction MGS Balongan (Hazardous Construction) has a value of direct lightning strike frequency (Nd) of 0.03 lightning strikes per year with an equivalent area of building lightning strikes (Ae) of 1082.95 m2. The value (Ng) of the intensity of lightning strikes to the ground is 27.6 lightning strikes per km2 per year, the protection level is level II with a radius of 30 meters and the earth resistance value is 0.344 Ω. The design value of this calculation is in accordance with PUIL 2011 standards, namely it must be below 5Ω for the overall value of earth resistance.